Characteristics and Clinical Course of Adult Inpatients with SARS-CoV-2 Pneumonia at High Altitude - Javier Leonardo Galindo; Juan Ricardo Lutz; María Alejandra Izquierdo; Katherine Parra; Lina María Prieto; Jorge Alberto Carrillo (Canadian Respiratory Journal)
Background. SARS-CoV-2 has spread worldwide with different dynamics in each region. We aimed to describe the clinical characteristics and to explore risk factors of death, critical care admission, and use of invasive mechanical ventilation in hospitalized patients with SARS-CoV-2 pneumonia in a high-altitude population living in Bogotá, Colombia. Methods. We conducted a concurrent cohort study of adult patients with laboratory-confirmed SARS-CoV-2 pneumonia. Demographic, clinical, and treatment data were extracted from electronic records. Univariate and multivariable methods were performed to investigate the relationship between each variable and outcomes at 28 days of follow-up. Results. 377 adults (56.8% male) were included in the study, of whom 85 (22.6%) died. Nonsurvivors were older on average than survivors (mean age, 56.7 years [SD 15.8] vs. 70.1 years [SD 13.9]; p≤0.001) and more likely male (28 [32.9%] vs. 57 [67.1%]; p=0.029). Most patients had at least one underlying disease (333 [88.3%]), including arterial hypertension (149 [39.5%]), overweight (145 [38.5%]), obesity (114 [30.2%]), and diabetes mellitus (82 [21.8%]). Frequency of critical care admission (158 [41.9%]) and invasive mechanical ventilation (123 [32.6%]) was high. Age over 65 years (OR 9.26, 95% CI 3.29–26.01; p≤0.001), ICU admission (OR 12.37, 95% CI 6.08–25.18; p≤0.001), and arterial pH higher than 7.47 (OR 0.25, 95% CI 0.08–0.74; p=0.01) were independently associated with in-hospital mortality. Conclusions. In this study of in-hospital patients with SARS-CoV-2 pneumonia living at high altitude, frequency of death was similar to what has been reported. ICU admission and use of invasive mechanical ventilation were high. Risk factors as older age, ICU admission, and arterial pH were associated with mortality.